To 90th Anniversary of Valentina S. Drozdovskaia (Ukrainian Journal of Ophthalmology, 2026)
hrough the 90th birth anniversary, 67 years of practicing medicine and scientific and teaching activities, she is in line so far! You must admit that it is not every day that we have a joyful occasion to congratulate such an anniversary celebrant. Valentina S. Drozdovskaia, the eldest ophthalmologists of Ukraine, was born on October, 18, 1926, in a village of Efimovka in Sumy region in a family of teachers. The youth of hers came in the years of Great Patriotic War; she survived bombing and all horrors of fascist occupation.